Pendampingan Preservasi dan Konservasi Bahan Pustaka di Perpustakaan SMP Swasta Nasrani Belawan Medan - Harefa, Hilda Syaf'aini; Sirait, Ronnie Togar Mulia; Ginting, Maretta (Fakultas Ushuluddin, Adab, dan Dakwah, 2024)
Libraries are increasingly developing into institutions that have an important role in collecting or preserving various forms of library materials. The impact of this is of course that every library must carry out the task of preserving or preserving various forms of library materials owned to anticipate the threat of damage which could result in the loss of intellectual content in these library materials. In practice, collection preservation activities are not only the responsibility of librarians. Ideally, it also requires awareness of users who utilize and use the collection. The aim of this activity is to increase understanding regarding the preservation and conservation of library materials and improve skills related to the preservation and conservation of library materials. The results of this activity are a) The implementation of community service went smoothly in accordance with the expectations of the team implementing community service, because almost all preservation actions were carried out, namely including preventive actions by implementing non-formal education for librarians, cleaning dusty library materials , regulating room temperature humidity, carrying out weeding of collections, tutorials on repackaging information and restorative actions by carrying out binding and lamination activities on damaged physical book collections, b) Participants are aware of the importance of preservation and conservation of library materials in preserving library materials owned by the library, c) Participants' responses to this activity stated that the delivery of the material was good and participants understood the explanation given. This is demonstrated by an interactive atmosphere between participants and the service team, as well as d) increasing insight both theoretically and practically regarding preservation and conservation procedures.